Etika Lingkungan dan Keadilan Antar Generasi: Membangun Respons Berkelanjutan Terhadap Perubahan Iklim - Ainia, Dela Khoirul; Kala Mahaswa, Rangga; Lasiyo; Arianto, Bagus (Jurnal Ekologi, Masyarakat dan Sains, 2025)
Climate change has impacted the sustainability of human life in the world both for the survival of current humans and future generations.  The purpose of writing this article is to explain the role of environmental ethics and intergenerational justice in responding to climate change so as to realize a sustainable life for the future. The method used is a qualitative method supported by sources of scientific articles, journals, research reports that support and are related to the main discussion. The results of the research show that environmental ethics and intergenerational justice have contributed to efforts to change the way humans view nature and climate change. The occurrence of climate change is partly caused by excessive human activities without paying attention to aspects of environmental balance. In addition, the views of environmental ethics and intergenerational justice can be integrated through policies in natural resource management so as to consider the sustainability of future life. Policies related to climate change need to be implemented and reflect intergenerational justice that is sustainable for the future.that is sustainable for the future. Thus, environmental ethics and intergenerational justice have a strong relationship with the environment.